Effects of different inoculants on the microstructural characteristics of gray cast iron gg-25, hardness and useful life of tools - Martin, Diego Ruben; Moreno, Joao Roberto Sartori; Vicente, André de Albuquerque (Acta Scientiarum. Technology, 2015)
Current study evaluated the machinability characteristics of parts, microstructure and mechanical properties when three different inoculants (IM-22 with FeSi-Ba/Zr; G-20 and FeSi-Ba; IMSR 75 with FeSi-Sr) were added in experiments carried out in a foundry. The research methodology was mailly based on the analysis of the machinability by the milling process of the specimens in gray cast iron GG-25, name according to DIN EN 1561.Evaluation of results is based on a thorough analysis of tool wear, surface finish, microstructural analysis, chemical composition and mechanical properties of the material. Results showed that among the studied inoculants strontium sulfide (SrS) was thermodynamically more stable than the others, because it leds towards a more negative free energy change of Gibbs and therefore more favorable to the formation of nuclei having greater critical radius (rc), solidification with heterogeneous nucleation. Its inoculant was also more efficient in forming a more favorable microstructure, greater amounts of eutectic cells and, longer life of the insert when machined.